2017
DOI: 10.1074/jbc.m116.773051
|View full text |Cite
|
Sign up to set email alerts
|

Neuropilin-1 mediates neutrophil elastase uptake and cross-presentation in breast cancer cells

Abstract: Neutrophil elastase (NE) can be rapidly taken up by tumor cells that lack endogenous NE expression, including breast cancer, which results in cross-presentation of PR1, an NE-derived HLA-A2-restricted peptide that is an immunotherapy target in hematological and solid tumor malignancies. The mechanism of NE uptake, however, remains unknown. Using the mass spectrometry-based approach, we identify neuropilin-1 (NRP1) as a NE receptor that mediates uptake and PR1 cross-presentation in breast cancer cells. We demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 41 publications
2
31
0
Order By: Relevance
“…Recent studies have provided evidence that tumor-associated neutrophils can be used as prognostic markers and regulate breast cancer metastasis [ 47 , 48 , 49 ]. Our current data demonstrate that breast cancer cells can influence neutrophils to facilitate cancer progression and metastasis through different complex mechanisms, and these mechanisms can differ between chemotherapy-resistant and parental breast tumor microenvironments.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have provided evidence that tumor-associated neutrophils can be used as prognostic markers and regulate breast cancer metastasis [ 47 , 48 , 49 ]. Our current data demonstrate that breast cancer cells can influence neutrophils to facilitate cancer progression and metastasis through different complex mechanisms, and these mechanisms can differ between chemotherapy-resistant and parental breast tumor microenvironments.…”
Section: Discussionmentioning
confidence: 99%
“…These data also point to tissue-specificity of CG uptake, since we have shown that breast cancer cells do not take up CG ( 25 ), which could be due to a shared receptor between distinct tumor types that facilitates the uptake of serine proteases ( 43 ). Our results also indicate that the efficiency and rate of CG uptake varies between different cell lines.…”
Section: Discussionmentioning
confidence: 91%
“…Additionally, this agent has potential therapeutic value as a treatment for solid cancers as well. Previously, we have shown that PR1/HLA-A2 is present on certain solid tumors such as breast cancer, lung cancer, and melanoma (14, 28, 29) via the mechanism of cross-presentation. This further expands a spectrum of diseases that can be treated with the 8F4 bi-specific antibody.…”
Section: Discussionmentioning
confidence: 99%